A organização do cuidado em saúde bucal de cidades da primeira macroregional de saúde da Paraíba - Cruz, Danilson Ferreira da (2010)
The present study investigated the organization of oral health care in the municipalities of Bayeux, Cabedelo, Guarabira, João Pessoa, Mamanguape, Santa Rita and Sapé, belonging to the Paraiba s 1st Macro-regional of Health. This was an exploratory descriptive study which had quantitative and qualitative approaches. The sample aimed at representing the First Macro-region of Health, since it is the most populous one in the state (1,726,022 inhabitants). Due to this study be part of a larger project, it was opted, for convenience, to work on the seven most populous cities and with the best accessibility, which composed the study sample. It represented 62.61% of the macro-regional s population. Data were gathered from two fronts: information systems: Primary Care Information System (PCIS); Ambulatory Information System of the Unified Health System (AIS / UHS); Public Budget in Health Information System (PBHIS), besides the interviews applied to users, workers and managers of the UHS from the municipalities that composed the sample. For this, the instrument for data collection consisted of two semi-structured interview scripts. Data obtained from the interviews were analyzed through the content analysis technique proposed by Bardin (2002), which is based on operations of dismemberment of the text into units or, in other words, on finding out the different units of meaning that constitute the communication and then doing their reunification into classes or categories. Descriptive analysis was also performed by means of graphs and tables of the indicators of oral health care and discursive association with socioeconomic indicators, funding and service supplies. From the results it was verified that municipalities showing the best socioeconomic indicators were the ones that most invested in health funding. Users who access the system through Primary Care are followed to another complexity level when they need to be referenced, which is indispensable for a Care Line, but the findings of this study indicated that there is not always a real concern with the guarantee of that continuity by the municipalities. The cities presenting the best indicators of Primary Care (access, coverage by the Family Health Team, collective action of brushing), are the most devoid of secondary offerings. It s concluded that the findings of this study might be used to assist managers from the municipalities of the Paraiba s 1st Macro-regional of Health in redirecting or maintaining the current oral health policies, in a socially oriented way according to the health needs of individual and collective subjects through the use of publically available secondary data and of the subjectivity of the social actors who constitute the UHS (managers, workers and users).